Level of functionality and disability in women with borderline personality disorder - Medina Torres, Juan Daniel; Torres Castillo, Maria Eugenia; Cortes Riveroll, José Gaspar Rodolfo; Arévalo Ramirez, Minou del Carmen (Horizonte Sanitario, 2025)
Objective: Borderline Personality Disorder (BPD) is a complex condition characterized by intense and unstable emotions, fluctuating relationships, and a distorted self-image, which lead to impulsive behaviors and difficulties in emotional regulation. In this study, we aimed to identify the level of functionality and disability in female patients diagnosed with BPD at the General Hospital of Zone 20 of the Mexican Institute of Social Security(IMSS) in Puebla (HGZP-20). Material and methods: A cross-sectional study was conducted at HGZP-20 between January and June 2023, in the outpatient psychiatry clinic, involving women diagnosed with BPD using the WHODAS 2.0 and the GAF scale. Results: A total of 200 female patients were included, with a mean age of 37 years. The most frequent psychiatric comorbidity was depression (57%). We found that 45.5% of the patients had never received psychotherapy, highlighting the need to improve therapeutic interventions. Seventy-four percent had a GAF score equal to or greater than 70, indicating an acceptable level of global functioning; however, 88.5% of the patients showed mild to moderate disability, revealing a discrepancy between objective evaluation and subjective perception. Conclusions: The use of clinimetric tools is crucial for implementing early and targeted therapeutic interventions aimed at improving medical care and the quality of life of patients with BPD. Keywords: Disability Evaluation; Personality Disorders; Borderline Personality Disorder; Psychiatry; Women.